Rust resistance in Mucuna pruiens accessions - and S.V. NGACHAN, P. BAISWAR*, K.P. MOHAPATRA, P. CHANDRA (Indian Phytopathology, 2018)
Mucuna is considered to be an important source of chemical which is useful in Parkinson’s disease and other neurological disorders. Mucuna accessions collected from various agroecological zones were screened for rust resistance at ICAR Research Complex for NEH region in Meghalaya. Only three accessions viz. WBN 3, WBN 6 and NGL 25 were identified as highly resistant. Seven accessions were found to be resistant and nineteen accessions were found to be moderately resistant. These accessions can be used in future breeding programs of this important crop.